2008
DOI: 10.1080/02640410802199789
|View full text |Cite
|
Sign up to set email alerts
|

Maximal oxygen uptake versus maximal power output in children

Abstract: Maximal oxygen uptake (VO 2PEAK ) is considered the optimal method to assess aerobic fitness.Such measurements, however, require special equipment and training. Maximal exercise test with determination of maximum power output (max W) offers a more simple approach. This study explores the relationship between VO 2PEAK and max W in 247 children (139 boys and 108 girls), aged 7.9-11.1 years. VO 2PEAK was measured by indirect calorimetry during a maximal ergometer exercise test with an initial workload of 30 W and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 33 publications
3
41
0
1
Order By: Relevance
“…However, it is important to mention that there is a distinction between these two variables. VO 2peak is a measure of aerobic fitness, whereas W peak is a combined measure of both aerobic and anaerobic fitness (11). Since children have an underdeveloped anaerobic energy system (19), the anaerobic energy contribution to the total work performed might be small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to mention that there is a distinction between these two variables. VO 2peak is a measure of aerobic fitness, whereas W peak is a combined measure of both aerobic and anaerobic fitness (11). Since children have an underdeveloped anaerobic energy system (19), the anaerobic energy contribution to the total work performed might be small.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson's correlations were determined between predicted and measured VO 2peak . Finally, our prediction equation was compared with that of the equation by Dencker et al by entering the individual test results from the children with JIA recruited in this study into the mixed-gender equation by Dencker et al (11). All statistical analyses were performed in SPSS, version 15.0 (SPSS).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, direct measurement of VO 2PEAK is considered the optimal method for assessment of aerobic fitness since all other methods introduces errors [14]. have misclassified a limited number of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment and methodology of the study cohort has been presented previously [9][10][11][12][13][14][15]. In brief, 477 children (259 boys and 218 girls) living in homogenous middle class areas in Malmö, Sweden, received an invitation to participate in the study and 248 (140 boys and 108 girls) accepted the invitation.…”
Section: Subjects and Anthropometric Measuresmentioning
confidence: 99%
“…It is important to provide reference values for cardiovascular fitness and responses of heart rate (HR) and systolic blood pressure (SBP) to maximal exercise test in children to be able to evaluate the cardiovascular function and health of children and to detect those with abnormal values (Paridon et al, 2006). Although there are a few population studies on cardiovascular fitness or haemodynamic responses to maximal exercise test in healthy children (Dencker et al, 2008;Eiberg et al, 2005;Ten Harkel, Takken, Van Osch-Gevers, & Helbing, 2011), none of them have reported cardiovascular fitness and changes in HR and SBP during and after exercise test.…”
Section: Introductionmentioning
confidence: 96%